An analysis of the Special Testimony and Specialized Listening as mechanisms for the preservation of children and adolescents victims of sexual violence (Research, Society and Development, 2021)
This article aimed to analyze the implications of Law 13,431 of 2017, which establishes certain guarantees for the rights of children and adolescents, victims or witnesses of violence and amends the Statute of Children and Adolescents, Law 8,069, of July 13, 1990. The research problem exposed consists of analyzing the technique of personal testimony, an alternative method of interrogating victims of sexual abuse, fulfilling the function for which it was created, that is, avoiding the re-victimization of children and adolescents victims of intrafamily sexual abuse. . To achieve the purposes of the study, initially, in the first section, a general approach was made on the rights of children and adolescents and the main legislation for their protection. Then, in the second section it deals with an approach on the types of violence and in the last section it does a research about the specific study of specialized listening and the special testimony, bringing the main changes of the legislation in this sense and analyzing the possible benefits of these instruments for victims of sexual abuse. The methodology is based on a qualitative bibliographic approach, using the hypothetical-deductive as the research method and the historical-comparative as the method of approach. As a result of this research, it was possible to verify that the creation of new hearing mechanisms has the central objective of protecting children and adolescents if they avoid a possible revictimization through the application of specialized listening and special testimony.